THE INFLUENCE OF ANTI-CORRUPTION EDUCATION ON STUDENTS' ATTITUDES AND INTEGRITY BEHAVIOR IN HIGHER EDUCATION INSTITUTIONS - Gufran Gufran; Rostati Rostati (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze the influence of anti-corruption education on students' attitudes and integrity behavior in higher education. A mixed methods approach was applied, combining questionnaires, surveys, interviews, and observations. A total of 104 students completed qualitative questionnaires, and 142 students participated in quantitative surveys. The findings reveal that most students understand the importance of anti-corruption education (94.4%) and consider it relevant to academic life (89.4%). Furthermore, 88.8% of students reject academic misconduct such as cheating and proxy attendance, while 85.9% expressed readiness to act as anti-corruption agents both on campus and in society. Qualitative data also highlight positive changes in honesty, discipline, and responsibility. This study concludes that anti-corruption education effectively raises awareness, shapes character, and encourages students to internalize integrity values in both academic and social contexts.